Trudnoe reshenie Eduarda Shevarnadze . Trudnoe reshenie Eduarda Shevarnadze . Difficult Decision of Eduard Shevarnadze . Трудное решение Эдуарда Шеварнадзе - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The Georgian President talks about his negotiations with the Russian President, and reflects on the Georgian-Ossetian conflict and on the prospects for Georgian-Russian relations. Президент Грузии рассказывает о переговорах с президентом России и рассуждает о грузино-осетинском конфликте и о перспективах взаимоотношений Грузии и России.